Comparison of infection and human immune responses of two SARS-CoV-2 strains in a humanized hACE2 NIKO mouse model - Yong, Kylie Su Mei; Anderson, Danielle E.; Zheng, Adrian Kang Eng; Liu, Min; Tan, Sue Yee; Tan, Wilson Wei Sheng; Chen, Qingfeng; Wang, Lin-Fa (Scientific reports, 2023)
The COVID-19 pandemic has sickened millions, cost lives and has devastated the global economy. Various animal models for experimental infection with SARS-CoV-2 have played a key role in many aspects of COVID-19 research. Here, we describe a humanized hACE2 (adenovirus expressing hACE2) NOD-SCID IL2Rγ −/− (NIKO) mouse model and compare infection with ancestral and mutant (SARS-CoV-2-∆382) strains of SARS-CoV-2. Immune cell infiltration, inflammation, lung damage and pro-inflammatory cytokines and chemokines was observed in humanized hACE2 NIKO mice. Humanized hACE2 NIKO mice infected with the ancestral and mutant SARS-CoV-2 strain had lung inflammation and production of pro-inflammatory cytokines and chemokines. This model can aid in examining the pathological basis of SARS-CoV-2 infection in a human immune environment and evaluation of therapeutic interventions.